“Química em geral” a partir de uma tabela periódica no microsoft excel: uma estratégia de ensino de química na educação básica - Carreira, Wanderley (2010)
The product of this work is the result of a qualitative and quantitative research applied that was aimed to develop a resource for the teaching of chemistry, from a periodic table developed in Microsoft Excel - T Wanc®© resulted in an interpretative analysis of different instruments under which the teaching of chemistry is founded, such as the Brazilian Law of Directives and Bases of National Education (LDBEN), the Brazilian National Curriculum Parameters for Secondary Education (PCNEM) Curriculum Guidelines for High School, chemistry books in the National Textbook Program for high school (PNLEM) and websites dedicated to the Periodic Table. Later, participants discussed the limitations of books and selected sites in the light of context and interdisciplinarity has established a dialogue between the Periodic Table and issues such as toxicology, geology, ecology, nutrition, physiology, among others, culminating in a didactic proposal with a different approach from that commonly practiced by the textbooks. The evaluation of the proposed application (T Wanc®© content in question, signaled the possibility of its use as a teaching tool in chemistry class in basic education.